Efektifitas Metode Muraja’ah dalam Menghafal Al-Qur’an pada Santri Pondok Pesantren - Abdul Khamid; Rofiqotul Munifah; Aida Dwi Rahmawati (Institut Agama Islam Negeri Kendari, 2021)
This article aims to present the results of a qualitative research that explores the impact of muraja'ah method in memorizing the Qur'an and to determine the supporting and inhibiting factors during its application in one of the Islamic boarding schools in East Java. Data was collected through observation, interviews, and documentation. The results of data analysis showed that the implementation of memorizing the Qur'an with the Muraja'ah method in this study was using the One Day One Page system with memorizing new muraja'ah to the ustadzah, muraja'ah the previous memorization with pairs, muraja'ah the previous memorization to the teacher, and the memorization test. In this study, the muraja'ah method was considered effective. The supporting factors in this research are discipline, memorization targets, motivation from parents and teachers, achievement logs, prayers for success in memorizing the Qur’an. The inhibiting factors for the application of the muraja'ah method in this study were the forgotten verses, feeling lazy, or tired. The solution to overcome these obstacles is rote repetition, self-motivation, and time management.Keywords: Islamic boarding school; memorization; muraja’ah; One Day One Page; student